1984
DOI: 10.1007/bf02744002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mechanical deformation: Exoemission

Abstract: An introduction to some of the physical effects (e.0. exoemission, acoustic emission and mechanoluminescence) associated with the mechanical deformation of solids is presented. Greater emphasis has been given to exoelectron emissions. Experimental information and plausible mechanisms for exoemission have been described briefly. In particular, exoelectron emission from metals and oxide-coated metals has been discussed at some length, with the hope of generating a common interest among physicists and metallurgis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…This can also result in the PTSE maxima. [25] Thermal destruction of vacancy-interstitial pair defects in Al 2 O 3 can begin already at temperatures above 100 C. [26][27][28] In addition, photostimulation of the oxide during exoelectron emission measurements can further recharge point defects and lead to the delocalization of electrons. [29] Surface morphology of the films after heating was analyzed using SEM.…”
Section: Resultsmentioning
confidence: 99%
“…This can also result in the PTSE maxima. [25] Thermal destruction of vacancy-interstitial pair defects in Al 2 O 3 can begin already at temperatures above 100 C. [26][27][28] In addition, photostimulation of the oxide during exoelectron emission measurements can further recharge point defects and lead to the delocalization of electrons. [29] Surface morphology of the films after heating was analyzed using SEM.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanical degradation mechanisms are mostly associated with volume changes and stress generated during Li de/-intercalation in an active material (i.e., cathode or anode). As a result of volume changes and stress generated, active particles may form cracks, lose contact from each other or the current collector, and become isolated [21][22][23]. In addition, it was shown that stress generated during cycling of a battery alters the pore structure of a separator and results in lower Li ion mobility [24,25].…”
Section: Introductionmentioning
confidence: 99%